Staphylococcus aureus induces tolerance in human monocytes accompanied with expression changes of cell surface markers - Müller, Mario M.; Baldauf, Christian; Hornischer, Stella; Klassert, Tilman E.; Schneegans, Antony; Behnert, Andrea; Pletz, Mathias W.; Hagel, Stefan; Slevogt, Hortense (Frontiers in Immunology, 2023)
Exposure of human monocytes to lipopolysaccharide (LPS) or other pathogen-associated molecular pattern (PAMPs) induces a temporary insensitivity to subsequent LPS challenges, a cellular state called endotoxin tolerance (ET), associated with the pathogenesis of sepsis.. In this study, we aimed to characterize the cellular state of human monocytes from healthy donors stimulated with Staphylococcus aureus in comparison to TLR2-specific ligands. We analyzed S. aureus induced gene expression changes after 2 and 24 hours by amplicon sequencing (RNA-AmpliSeq) and compared the pro-inflammatory response after 2 hours with the response in re-stimulation experiments. In parallel, glycoprotein expression changes in human monocytes after 24 hours of S. aureus stimulation were analyzed by proteomics and compared to stimulation experiments with TLR2 ligands Malp-2 and Pam3Cys and TLR4 ligand LPS. Finally, we analyzed peripheral blood monocytes of patients with S. aureus bloodstream infection for their ex vivo inflammatory responses towards S. aureus stimulation and their glycoprotein expression profiles. Our results demonstrate that monocytes from healthy donors stimulated with S. aureus and TLR ligands of Gram-positive bacteria entered the tolerant cell state after activation similar to LPS treatment. In particular reduced gene expression of pro-inflammatory cytokines (TNF, IL1β) and chemokines (CCL20, CCL3, CCL4, CXCL2, CXCL3 and CXCL8) could be demonstrated. Glycoprotein expression changes in monocytes tolerized by the different TLR agonists were highly similar while S. aureus-stimulated monocytes shared some of the PAMP-induced changes but also exhibited a distinct expression profile. 11 glycoproteins (CD44, CD274, DSC2, ICAM1, LAMP3, LILRB1, PTGS2, SLC1A3, CR1, FGL2, and HP) were similarly up- or downregulated in all four comparisons in the tolerant cell state. Monocytes from patients with S. aureus bacteremia revealed preserved pro-inflammatory responsiveness to S. aureus stimulation ex vivo, expressed increased CD44 mRNA but no other glycoprotein of the tolerance signature was differentially expressed.